Penguatan Kurikulum, Sistem Pendukung, dan Lingkungan Sosial Sekolah dalam Menumbuhkan Tradisi Toleransi dan Penghargaan Identitas Peserta Didik - Masfufah; Didit Darmawan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Multicultural education in schools becomes an important milestone to shape a tolerant generation in an era of plural society. This study aims to analyze the understanding and commitment of educational stakeholders, namely teachers, school management, and the community, to implement multicultural education as a response to issues of intolerance. This study uses a qualitative approach through literature review and thematic synthesis. Data analysis is conducted through thematic analysis on all research data. This study finds that the main factors supporting the success of multicultural education are a responsive curriculum renewal, practice-based teacher training, the formation of inclusion teams, strengthening social networks, and the integration of digital media use as a learning medium. Constructive collaboration among parties within the school environment, as well as family and community involvement, has proven vital for realizing the internalization of values of tolerance and respect for differences in identity among students. These findings underline the importance of synergy across educational elements and the need for policies that are responsive and adaptive to global social and technological dynamics. This study also recommends strengthening multicultural learning innovations